Design a Solar Powered Stirling Engine Prototype to Produce Electricity - Lee Shee Yao; Hanani Abdul Wahab (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2020)
For the concerns of environmental issue such as global warming, sustainable and green way to produce energy is highly in demand. Dish Stirling system is one of the most efficient system among others concentrated solar power technologies. However, the system is in disadvantage in terms of cost and reliability when compare to others CSP technologies. In this study, a fundamental prototype of solar powered dish Stirling engine is designed, manufactured, and tested. One component of the prototype which is the power piston is malfunctioning. It was found that the accuracy requirement of the manufacturing of the prototype was high and it requires high skill and experience in machining process.